The Implications of Breast Cancer Molecular Phenotype for Radiation Oncology - Sioshansi, Shirin; Huber, Kathryn E.; Wazer, David E. (Frontiers in Oncology, 2011)
The identification of distinct molecular subtypes of breast cancer has advanced the understanding and treatment of breast cancer by providing insight into prognosis, patterns of recurrence and effectiveness of therapy. The prognostic significance of molecular phenotype with regard to distant recurrences and overall survival are well established in the literature and has been readily incorporated into systemic therapy management decisions. However, despite the accumulating data suggesting similar prognostic significance for locoregional recurrence, integration of molecular phenotype into local management decision making has lagged. Although there are some conflicting reports, collectively the literature supports a low risk of local recurrence in the hormone receptor positive luminal subtypes compared to hormone receptor negative subtypes (triple negative and HER2-enriched). The development of targeted therapies, such as trastuzumab for the treatment of HER2-enriched subtype, has been shown to mitigate the increased risk of local recurrence. Unfortunately, no such remedy exists to address the increased risk of local recurrence for patients with triple negative tumors, making it a clinical challenge for radiation oncologists. In this review we discuss the correlation between molecular subtype and local recurrence following either breast conservation therapy or mastectomy. We also explore the possible mechanisms for increased local recurrence in triple negative breast cancer and radiotherapeutic implications for this population, such as the safety of breast conservation, consideration of dose escalation and the appropriateness of accelerated partial breast irradiation.